Dielectric and voltage-sensitive bifunctional ceramic and preparation method thereof

The (Y0.5+xBi0.5-x)2/3Cu3Ti4O12 ceramic material was synthesized by hydrothermal synthesis method, and its microstructure was adjusted, which solved the problem of difficult to harmonize the dielectric constant and dielectric loss of existing ceramic materials, and achieved high dielectric constant, low dielectric loss and high voltage sensitive ceramic materials.

CN119504254APending Publication Date: 2025-02-25ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411625782.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

While existing high-dielectric constant ceramic materials reduce dielectric loss, their dielectric constant also decreases, and it is difficult to have excellent dielectric and voltage-sensitive properties in the same material at the same time.

Method used

(Y0.5+xBi0.5-x)2/3Cu3Ti4O12 ceramic material was synthesized by hydrothermal synthesis method, and the microstructure of the ceramic was adjusted to take into account the grain size and grain boundary thickness, thereby obtaining high dielectric constant, low dielectric loss and high voltage sensitivity.

Benefits of technology

It realizes the huge dielectric constant (>104), low dielectric loss (<0.05), high breakdown field strength and nonlinear coefficient of ceramic materials, and has excellent dielectric and voltage-sensitive dual-functional performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504254A_ABST
    Figure CN119504254A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of dielectric and pressure-sensitive materials, discloses dielectric and pressure-sensitive bifunctional ceramic and a preparation method thereof, and is used for solving the technical problem that the dielectric and pressure-sensitive bifunctional ceramic cannot have excellent dielectric constant, dielectric loss, breakdown field strength and nonlinear coefficient at the same time. The ceramic material is represented by (Y < 0.5 + x > Bi < 0.5-x >) < 2 / 3 > Cu3Ti4O12, wherein x is greater than or equal to-0.1 and less than or equal to 0.1. Yttrium oxide, bismuth oxide, copper acetate and titanium oxide are used as starting raw materials and mixed according to the chemical formula proportion, ethylenediamine is added, the mixture is stirred at the room temperature and then subjected to heat preservation for a certain time, ceramic powder is obtained, and the ceramic material is obtained after separation, cleaning, drying, tabletting and sintering. The dielectric constant of the prepared ceramic material at 10 kHz can reach 14250, the dielectric loss is as low as 0.017, the breakdown field strength reaches 17.8 kV / cm, and the nonlinear coefficient is 7.9. The ceramic material has important application prospects in the fields of high-capacity capacitors, high-energy density storage, piezoresistors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of dielectric and varistor materials, and in particular relates to a dielectric ceramic material. Background Art

[0002] Dielectric ceramic materials with high dielectric constant and low dielectric loss have important applications in the miniaturization of electronic devices, dynamic random access memory, 5G communications and energy storage, and have important application prospects in the development of information technology and new energy. Common high dielectric constant materials include barium strontium titanate and lead zirconate titanate. The former has a temperature-instability crystal structure and is prone to phase change, which affects the performance of the material. The latter contains lead, an environmentally unfriendly material, and is criticized. Calcium copper titanate (ACu3Ti4O 12 ,ACTO(A=Ca,Cd,Bi 2 / 3 ,Y 2 / 3 The dielectric constant of ceramic materials is as high as 10 3 -10 4 , has good temperature stability at 100-600K, no structural phase change, and is expected to be widely used in the above-mentioned fields. In addition, ACTO ceramic material also has good varistor properties and can be used as a varistor. However, ACTO has a large dielectric loss (tanδ>0.05), which can easily lead to excessive energy consumption or even failure due to overheating of the device. In addition, during its modification process, the dielectric loss is reduced while the dielectric constant is also reduced. In addition, the dielectric and varistor properties are mutually exclusive, and it is difficult for the two excellent properties to coexist in the same material, which restricts its potential application.

[0003] Currently, it is still a challenge to design and develop dielectric and varistor dual-functional materials with high dielectric constant, low dielectric loss, high breakdown field strength and nonlinear coefficient. ACTO ceramics are composed of semiconducting grains and insulating grain boundaries. The dielectric constant is proportional to the grain size and inversely proportional to the grain boundary thickness. Large grain size often means thin grain boundaries, which is conducive to obtaining high dielectric constants. However, thin grain boundaries lead to high dielectric losses. At the same time, this structure will cause low breakdown field strength and nonlinear coefficient, deteriorating the performance of varistor. Yang Zupei and others from Shaanxi Normal University obtained Bi using the sol-gel method. 2 / 3 Cu3Ti4O 12 Ceramic material, the dielectric constant at 1kHz reaches 11000, the dielectric loss is 0.11, the breakdown field strength is 1.21kV / cm, and the nonlinear coefficient is 1.65. (L.Yang,X.Chao,Z.Yang,N.Zhao,L.Wei,Z.Yang,Dielectric constant versus voltage and non-Ohmic characteristics of Bi2 / 3Cu3Ti4O 12 ceramics prepared by different methods, Ceram. Int. 42 (2016) 2526-2533.); In 2022, Sripusharawoot et al. from Khon Kaen University in Thailand prepared Y 2 / 3Cu3Ti4O 12 Ceramic, dielectric constant reaches 7600, dielectric loss is 0.10. (J.Boonlakhorn,S.Nijpanich,P.Thongbai,P.Srepusharawoot,High dielectric permittivity and dielectric relaxation behavior in a Y 2 / 3 Cu3Ti4O 12 ceramic prepared by a modified sol-gel route, Ceram. Int. 48 (2022) 15405-15413.). According to the phase diagram, ACTO is a point compound with a very narrow solubility. If its composition deviates slightly from the stoichiometry, the material will end along the binary system line or in the ternary field, resulting in a significant change in the ACTO microstructure. This provides a possibility for adjusting the ACTO microstructure by composition and thus improving the dielectric and varistor properties; however, high dielectric constant, low dielectric loss and excellent varistor properties are difficult to reconcile, which requires finding a perfect balance between grain size, grain boundary thickness and resistance, and grain boundary barriers. Therefore, it is not easy to have excellent dielectric properties and varistor properties in one material at the same time, which reflects the usefulness and potential application value of conducting research on related issues of such materials.

[0004] The main methods for preparing ceramics include solid-phase sintering, sol-gel, and hydrothermal synthesis. The solid-phase sintering method has a simple process, high energy consumption, and the density of the sintered ceramic material is poor. The sol-gel method has good uniformity of material composition and can effectively reduce the sintering temperature, but the synthesis of the sol is more complicated. The hydrothermal synthesis method can not only improve the uniformity of the composition, but also eliminate the pre-firing process of the powder, which can reduce the sintering energy consumption and is an ideal choice for preparing high-performance ceramics. Summary of the invention

[0005] In view of the above technical problems, the present invention proposes a dielectric and varistor dual-function ceramic and a preparation method thereof. The present invention synthesizes (Y 0.5+x Bi 0.5-x ) 2 / 3 Cu3Ti4O 12Ceramic material, which has a huge dielectric constant (>10 4 ), small dielectric loss (<0.05), very high breakdown field strength and nonlinear coefficient, thus obtaining a dual-functional ceramic material with excellent dielectric and varistor properties.

[0006] To achieve the above object, the technical solution of the present invention is implemented as follows:

[0007] A dielectric and varistor dual-function ceramic, the chemical formula of which is: (Y 0.5+x Bi 0.5-x ) 2 / 3 Cu3Ti4O 12 , where -0.1≤x≤0.1.

[0009] Further, its general chemical formula is: (Y 0.5+x Bi 0.5-x ) 2 / 3 Cu3Ti4O 12 , where -0.05≤x≤0.05.

[0010] The dielectric and varistor dual-function ceramic has a dielectric constant of 12090-14250, a dielectric loss of 0.017-0.041, a breakdown field strength of 15.7-17.8 kV / cm, and a nonlinear coefficient of 6.5-7.9 at room temperature and 10 kHz.

[0011] Further, when x=0, at room temperature and 10 kHz, the dielectric constant of the dielectric and varistor dual-function ceramic is 14250, the dielectric loss is 0.017, the breakdown field strength is 17.8 kV / cm, and the nonlinear coefficient is 7.9.

[0012] The present invention utilizes a hydrothermal synthesis method, uses yttrium oxide, bismuth oxide, copper acetate, and titanium oxide as starting materials, mixes them according to the component ratio, adds ethylenediamine, places them in a reactor at a certain temperature to react, and then separates, cleans, dries, granulates, tablets, removes binders, and heat treats to obtain ceramic materials. The specific steps are as follows:

[0013] (1) Yttrium oxide, bismuth oxide, copper acetate and titanium oxide are used as raw material powders, and the composition formula (Y 0.5+ x Bi 0.5-x ) 2 / 3 Cu3Ti4O 12 The ingredients are prepared to obtain a mixed powder; the mixed powder is mixed and stirred with ethylenediamine (C2H8N2), and then subjected to heat preservation reaction, separation, and washing to obtain a ceramic powder;

[0014] (2) adding a binder to the ceramic powder and granulating the powder, and then pressing the powder into a shape to obtain a ceramic body;

[0015] (3) The ceramic body is subjected to low-temperature debinding and heating and heat-insulating sintering treatments, and copper yttrium bismuth titanate ceramics are obtained after cooling.

[0016] In the above step (1), the molar ratio of the mixed powder to ethylenediamine is 1:(7-9), and the stirring time is 1-2h.

[0017] The temperature of the heat preservation reaction in the above step (1) is 190-210° C. and the time is 30-42 hours.

[0018] In the above step (2), the binder is polyvinyl alcohol; the pressure during the powder pressing is 8-10 MPa, the diameter of the ceramic body is 1.0-1.1 cm, and the thickness is 0.7-0.8 mm.

[0019] Furthermore, based on the mass of the ceramic powder, the added amount of polyvinyl alcohol is 1.5-2wt%.

[0020] In the above step (3), low-temperature debinding refers to heating the temperature to 480-520°C at a heating rate of 1-2°C / min and keeping it warm for 1-2 hours; heating and keeping sintering treatment refers to heating the temperature to 1050-1080°C at a heating rate of 2-3°C / min and keeping it warm for 12-18 hours; cooling refers to cooling the temperature to 500°C at a cooling rate of 3°C / min and then cooling with the furnace.

[0021] The principle that the ceramic material obtained by this process method has excellent dielectric and varistor properties is: a dense ceramic structure is obtained by hydrothermal synthesis, and an appropriate element combination at the A position is used to adjust the microstructure of the ACTO material. The microstructure of the ceramic takes into account both the grain size and the grain boundary thickness, so that it has a large grain size to obtain a huge dielectric constant, and at the same time has a highly insulating grain boundary to reduce dielectric loss. The high potential barrier of the grain boundary phase ensures the good varistor properties of the material. The finally prepared ceramic material has both excellent dielectric and varistor properties.

[0022] The above-mentioned dielectric and varistor dual-functional ceramics are used in the fields of large-capacitance capacitors, high-density energy storage or varistors.

[0023] The beneficial effects produced by the present invention are:

[0024] (1) Through appropriate atomic ratios and hydrothermal synthesis, a ceramic material with excellent dielectric and varistor dual functions was synthesized. The ceramic material has a huge dielectric constant (12090-14250), low dielectric loss (0.017-0.041), high breakdown field strength (15.7-17.8kV / cm) and nonlinear coefficient (6.5-7.9). Specifically, a dense ceramic structure was obtained by hydrothermal synthesis, and the appropriate element combination at the A position adjusted the microstructure of the ACTO material. The microstructure of the ceramic took into account both the grain size and the grain boundary thickness, so that it had a large grain size to obtain a huge dielectric constant, and at the same time had a highly insulating grain boundary to reduce dielectric loss. The high potential barrier of the grain boundary phase ensured the good varistor performance of the material. The copper yttrium bismuth titanate ceramic finally prepared has both excellent dielectric and varistor properties.

[0025] (2) The ceramic material adopts the hydrothermal synthesis method, which can not only improve the uniformity of the composition but also reduce the sintering process and reduce the sintering energy consumption. It has the advantages of simple preparation method, low cost, good repeatability and suitability for industrial production. It has important application value in the fields of large-capacity capacitors, high-density energy storage and varistors. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 These are the XRD patterns of the ceramic materials prepared in Examples 1-5 of the present invention.

[0028] Figure 2 XRD diagrams of ceramic materials prepared in Comparative Examples 1-4 of the present invention.

[0029] Figure 3 These are SEM images of ceramics prepared in Comparative Example 1 and Example 3 of the present invention; wherein (a) is Comparative Example 1, and (b) is Example 3.

[0030] Figure 4 The dielectric constant of the ceramics prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 varies with frequency.

[0031] Figure 5 The dielectric loss factor of the ceramics prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 varies with frequency.

[0032] Figure 6Impedance spectra of ceramic samples prepared for Examples 1-5 of the present invention and Comparative Examples 1-4.

[0033] Figure 7 The current density of the ceramic samples prepared in Examples 1-5 of the present invention and Comparative Examples 1-4 varies with the electric field strength. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.6 Bi 0.4 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0037] (1) According to the general composition formula (Y 0.6 Bi 0.4 ) 2 / 3 Cu3Ti4O 12 Y2O3 (0.2581 g), Bi2O3 (3.1064 g), C4H6CuO4 (1.19325 g), and TiO2 (1.5974 g) were mixed and the mixture was prepared according to the general formula (Y 0.6 Bi 0.4 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0038] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0039] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.6 Bi 0.4 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0040] The ceramics prepared in this embodiment were treated as follows and the electrochemical properties were tested. Specifically, the sintered ceramic samples were polished to 150 μm with sandpaper, silver paste was applied to the upper and lower surfaces of the ceramics, the temperature was raised to 350°C at 5°C / min and kept for 0.5h, cooled with the furnace, and the electrical properties were tested. The dielectric constant of the ceramic material prepared in this embodiment was tested to be 12090 at 10kHz, the dielectric loss was 0.032, the breakdown field strength was 16.1kV / cm, and the nonlinear coefficient was 6.8.

[0041] Example 2

[0042] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.4 Bi 0.6 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0043] (1) According to the general composition formula (Y 0.4 Bi 0.6 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.4 Bi 0.6 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0044] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0045] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.4 Bi 0.6 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0046] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this example at 10 kHz was measured to be 12570, the dielectric loss was 0.041, the breakdown field strength was 15.7 kV / cm, and the nonlinear coefficient was 6.5.

[0047] Example 3

[0048] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0049] (1) According to the general composition formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0050] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0051] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0052] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this example at 10 kHz was measured to be 14250, the dielectric loss was 0.017, the breakdown field strength was 17.8 kV / cm, and the nonlinear coefficient was 7.9.

[0053] Example 4

[0054] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.45 Bi 0.55 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0055] (1) According to the general composition formula (Y 0.45 Bi 0.55 ) 2 / 3 Cu3Ti4O 12Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.45 Bi 0.55 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0056] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0057] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.45 Bi 0.55 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0058] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this example at 10 kHz was measured to be 13200, the dielectric loss was 0.032, the breakdown field strength was 17.1 kV / cm, and the nonlinear coefficient was 7.2.

[0059] Example 5

[0060] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.55 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0061] (1) According to the general composition formula (Y 0.55 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.55 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0062] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0063] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.55 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0064] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this example at 10 kHz was measured to be 12780, the dielectric loss was 0.024, the breakdown field strength was 16.5 kV / cm, and the nonlinear coefficient was 7.0.

[0065] Example 6

[0066] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 By exploring the effect of the molar ratio of the mixed powder to ethylenediamine on the ceramic properties, the preparation method steps are as follows:

[0067] (1) According to the general composition formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:7, 1:8, 1:9, take C2H8N2 respectively, mix and stir for 1.5h, pour into the reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0068] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0069] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.5 Bi0.5 ) 2 / 3 Cu3Ti4O 12 Ceramics, the properties of which are shown in Table 1.

[0070] Table 1 Results of dielectric constant, dielectric loss, breakdown field strength and nonlinear coefficient at 10kHz

[0071]

[0072] From Table 1, we can see that when (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8, the prepared ceramic material has the best dielectric and varistor properties.

[0073] Example 7

[0074] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0075] (1) According to the general composition formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 190℃ for 42h, separate, wash and dry to obtain ceramic powder;

[0076] (2) adding 2 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 10 MPa to form a ceramic body with a diameter of 1.1 cm and a thickness of 0.8 mm;

[0077] (3) The ceramic body was heated to 480°C at a rate of 1°C / min and kept at that temperature for 2 hours to remove binder; then the temperature was raised to 1080°C at a rate of 2°C / min and kept at that temperature for 12 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0078] Example 8

[0079] The composition of the dielectric and varistor dual-function ceramic of this embodiment is (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0080] (1) According to the general composition formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 210℃ for 30h, separate, wash and dry to obtain ceramic powder;

[0081] (2) adding 1.75 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 9 MPa to form a ceramic body with a diameter of 1.1 cm and a thickness of 0.7 mm;

[0082] (3) The ceramic body was heated to 520°C at a heating rate of 1°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1050°C at a heating rate of 2°C / min and kept at that temperature for 18 hours, and then cooled to 500°C at a heating rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0083] Comparative Example 1

[0084] The composition of the copper bismuth titanate ceramic of this comparative example is Bi 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0085] (1) According to the general composition formula Bi 2 / 3 Cu3Ti4O 12 Take Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula Bi 2 / 3Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0086] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0087] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at this temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at this temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain Bi 2 / 3Cu3Ti4O 12 ceramics.

[0088] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this comparative example at 10 kHz was measured to be 9900, the dielectric loss was 0.1, the breakdown field strength was 2.75 kV / cm, and the nonlinear coefficient was 2.3.

[0089] Comparative Example 2

[0090] The composition of the copper yttrium titanate ceramic of this comparative example is Y 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0091] (1) According to the general composition formula Y 2 / 3 Cu3Ti4O 12 Mix Y2O3, C4H6CuO4 and TiO2 according to the general formula Bi 2 / 3Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0092] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0093] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at this temperature for 1 hour to remove the binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at this temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain Y 2 / 3Cu3Ti4O 12 ceramics.

[0094] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this comparative example at 10 kHz was measured to be 7500, the dielectric loss was 0.08, the breakdown field strength was 4.16 kV / cm, and the nonlinear coefficient was 3.0.

[0095] Comparative Example 3

[0096] The composition of the dielectric and varistor dual-function ceramic of this comparative example is (Y 0.65 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0097] (1) According to the general composition formula (Y 0.65 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.65 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0098] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0099] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.65 Bi 0.45 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0100] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this example at 10 kHz was measured to be 9400, the dielectric loss was 0.069, the breakdown field strength was 5.72 kV / cm, and the nonlinear coefficient was 3.5.

[0101] Comparative Example 4

[0102] The composition of the dielectric and varistor dual-function ceramic of this comparative example is (Y 0.45 Bi 0.65 ) 2 / 3 Cu3Ti4O 12 , and the preparation method steps are as follows:

[0103] (1) According to the general composition formula (Y 0.45 Bi 0.65 ) 2 / 3 Cu3Ti4O 12Take Y2O3, Bi2O3, C4H6CuO4, TiO2 and mix them according to the general formula (Y 0.45 Bi 0.65 ) 2 / 3 Cu3Ti4O 12 :C2H8N2=1:8 Take C2H8N2 and mix and stir for 1.5h, pour into a reaction kettle and keep warm at 200℃ for 36h, separate, wash and dry to obtain ceramic powder;

[0104] (2) adding 1.5 wt% polyvinyl alcohol binder into the ceramic powder, granulating it, and pressing it at 8 MPa to form a ceramic body with a diameter of 1.0 cm and a thickness of 0.7 mm;

[0105] (3) The ceramic body was heated to 490°C at a rate of 2°C / min and kept at that temperature for 1 hour to remove binder; then the temperature was raised to 1070°C at a rate of 3°C / min and kept at that temperature for 15 hours, and then cooled to 500°C at a rate of 3°C / min and cooled to room temperature in the furnace to obtain (Y 0.45 Bi 0.65 ) 2 / 3 Cu3Ti4O 12 ceramics.

[0106] According to the processing and testing method of Example 1, the dielectric constant of the ceramic material of this example at 10 kHz was measured to be 10200, the dielectric loss was 0.078, the breakdown field strength was 5.24 kV / cm, and the nonlinear coefficient was 3.2.

[0107] Implementation effect example

[0108] The crystal structure, microscopic morphology and electrochemical performance polarity of the ceramic samples prepared in the above Examples 1-5 and Comparative Examples 1-4 were tested and analyzed, and the results are as follows.

[0109] (1) Crystal structure

[0110] The crystal structure of ceramic materials was tested using a SmartLab SE X-ray diffractometer (Japan). The results are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the copper yttrium bismuth titanate ceramics prepared in the comparative example and the example are all single perovskite structures without the generation of a second phase.

[0111] (2) Microscopic morphology

[0112] The surface morphology of the ceramic material was tested using a JSM-7001F field emission scanning electron microscope (Japan). Figure 3 As shown. Figure 3 (a) SEM (Comparative Example 1) and Figure 3It can be seen from the SEM image (b) (Example 3) that both samples are very dense. The grain size of the comparative example is smaller and the grain boundary is thinner, while the grain size of Example 3 is larger and the grain boundary is thicker. This is the effect of composition adjustment, which is conducive to obtaining a high dielectric constant, low dielectric loss and a large breakdown field strength.

[0113] (3) Electrical properties

[0114] The electrochemical performance of the prepared ceramics was tested using the 4294A precision impedance analyzer (USA) and the KEITHLEY4200 test system (USA) produced by Agilent Technologies. First, a silver electrode was prepared on the surface of the prepared ceramic sample. Specifically, the sintered ceramic sample was polished to 150 μm with sandpaper, and silver paste was applied to the upper and lower surfaces of the ceramic. The temperature was raised to 350°C at 5°C / min and kept for 0.5h. The sample was cooled in the furnace, and the electrical performance test was performed. The relevant performance parameters were calculated using the following formula.

[0115] Dielectric constant: ε′=Cd / ε0A, C is the capacitance of the sample, d is the thickness of the sample, ε0 is the vacuum dielectric constant (8.85×10 -12 F / m), A is the electrode area.

[0116] Dielectric loss: tanδ = ε′ / ε″, ε″ is the imaginary part of the dielectric constant.

[0117] Nonlinear coefficient: α=log(J2 / J1) / log(E2 / E1), E1 and E2 are the electric field intensities corresponding to J1=0.1mA / cm and J2=1mA / cm respectively.

[0118] Breakdown field strength E b is the electric field strength when the current density is 1 mA / cm.

[0119] Grain boundary barrier (Φ b ) is obtained by the following formula: Where A,β,k b and T are Richardson constant, a constant related to the barrier width, Boltzmann constant and temperature, respectively.

[0120] Depend on Figure 4 It can be seen that the dielectric constant of the example sample is significantly higher than that of the comparative example, which is due to its larger grain size. Figure 5 It can be seen from the dielectric loss of the embodiment that the dielectric loss (at a frequency of 10kHz) is lower, which is related to the higher grain boundary resistance caused by the thicker grain boundary. Figure 6 The impedance spectrum can be confirmed. Figure 6 The larger the arc radius, the greater the grain boundary resistance. Figure 6It can be observed that the grain boundary resistance of the embodiment is significantly higher than that of the comparative example. Combined with the dielectric loss values ​​in each example, it can be found that the larger the grain boundary resistance, the smaller the dielectric loss of the sample. The arc radius of Example 3 is the largest, the grain boundary resistance is the highest, and thus the dielectric loss is the smallest, which is 0.017. Figure 7 The current density of the embodiment and the comparative example varies with the field strength. It can be seen from the figure that the breakdown field strength of the embodiment is significantly higher than that of the comparative example, and the embodiment 3 has the largest breakdown field strength of 17.8 kV / cm. The varistor performance is closely related to the grain boundary barrier. A high grain boundary barrier is conducive to good nonlinear performance. The grain boundary barrier results of the ceramic materials prepared in the embodiment and the comparative example are shown in Table 2.

[0121] Table 2 Barrier height values ​​of ceramic samples prepared in Examples 1-5 and Comparative Examples 1-4

[0122] sample Example 1 Example 2 Example 3 Example 4 Example 5 Grain boundary barrier (eV) 0.821 0.801 0.964 0.895 0.884 sample Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Grain boundary barrier (eV) 0.594 0.602 0.655 0.631

[0123] It can be seen from Table 2 that the barrier height of the example sample is significantly higher than that of the comparative example, which indicates that the change of the grain boundary has a significant improvement effect on the barrier height.

[0124] The above results show that the ceramic material of the embodiment has better dielectric and varistor properties. 0.5 Bi 0.5 ) 2 / 3 Cu3Ti4O 12 The ceramic has a dielectric constant of 14250, a dielectric loss of 0.017, a breakdown field strength of 17.8 kV / cm, and a nonlinear coefficient of 7.9 at 10 kHz, and achieves excellent dielectric and varistor dual functions, which is significantly higher than similar ceramic materials. The invention has the advantages of simple process, low cost, and good repeatability. The resulting ceramic products have very important application prospects in the fields of large-capacity capacitors, high-density energy storage, and varistors.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A dielectric and varistor dual-function ceramic, characterized in that: The chemical formula of the dielectric and varistor dual-function ceramic is: 0.5+x Bi 0.5-x ) 2 / 3 Cu3Ti4O 12 , where -0.1≤x≤0.

1.

2. The dielectric and varistor dual-function ceramic according to claim 1, characterized in that: The chemical formula of the dielectric and varistor dual-function ceramic is: 0.5+x Bi 0.5-x ) 2 / 3 Cu3Ti4O 12 , where -0.05≤x≤0.

05.

3. The dielectric and varistor dual-function ceramic according to claim 1, characterized in that: The dielectric and varistor dual-function ceramic has a dielectric constant of 12090-14250, a dielectric loss of 0.017-0.041, a breakdown field strength of 15.7-17.8 kV / cm, and a nonlinear coefficient of 6.5-7.9 at 10 kHz.

4. The method for preparing the dielectric and varistor dual-function ceramic according to claim 1, characterized in that: Here are the steps: (1) Yttrium oxide, bismuth oxide, copper acetate and titanium oxide are used as raw material powders, and the composition formula (Y 0.5+x Bi 0.5-x ) 2 / 3Cu3Ti4O 12 The ingredients are prepared to obtain a mixed powder; the mixed powder is mixed and stirred with ethylenediamine, and then subjected to heat preservation reaction to obtain ceramic powder; (2) adding a binder to the ceramic powder and granulating it, and then pressing the powder into a shape to obtain a ceramic body; (3) The ceramic body is subjected to low-temperature debinding and high-temperature sintering treatments, and then cooled to obtain copper yttrium bismuth titanate ceramics.

5. The method for preparing the dielectric and varistor dual-function ceramic according to claim 4, characterized in that: The molar ratio of the mixed powder to ethylenediamine in step (1) is 1:(7-9).

6. The method for preparing the dielectric and varistor dual-function ceramic according to claim 5, characterized in that: The temperature of the heat preservation reaction in step (1) is 190-210° C. and the time is 30-42 h.

7. The method for preparing the dielectric and varistor dual-function ceramic according to claim 6, characterized in that: Step (2) The binder is polyvinyl alcohol; the pressure during powder pressing is 8-10 MPa, the diameter of the ceramic body is 1.0-1.1 cm, and the thickness is 0.7-0.8 mm.

8. The method for preparing the dielectric and varistor dual-function ceramic according to claim 7, characterized in that: Based on the mass of the ceramic powder, the added amount of polyvinyl alcohol is 1.5-2 wt%.

9. The method for preparing the dielectric and varistor dual-function ceramic according to claim 7, characterized in that: Step (3) Medium and low temperature debinding refers to heating the temperature to 480-520℃ at a heating rate of 1-2℃ / min and keeping it warm for 1-2 hours; heating and keeping sintering treatment refers to heating the temperature to 1050-1080℃ at a heating rate of 2-3℃ / min and keeping it warm for 12-18 hours; cooling refers to cooling the temperature to 500℃ at a cooling rate of 3℃ / min and then cooling with the furnace.

10. Application of the dielectric and varistor dual-function ceramic according to claim 1 in the field of large-capacitance capacitors, high-density energy storage or varistors.